Phänomen Hörbuch -- Interdisziplinäre Perspektiven und medialer Wandel - Bung, Stephanie; Schrödl, Jenny (Edition Kulturwissenschaft, 2016)
In recent years in the German-speaking world, the audiobook has gained in popularity and significance. One can scarcely imagine libraries and bookstores without them - and academic research is also showing a growing interest. At the same time, it is a phenomenon which needs to be outlined in more detail. As the word audiobook already implies, it is a multifaceted object, which not only addresses various senses at the same time, but also changes form depending on our vantage point. The essays in this volume focus on this polymorphic quality, at the interface of various disciplines.